Batswana - Bolaane, Maitseo; Mgadla, Part Themba (New York : Rosen Pub. Group, 1997)
Surveys the history, culture, and contemporary life of the Batswana people of Botswana and South Africa.
Keywords: Tswana (African people) -- History -- Juvenile literature; Tswana (African people) -- Social life and customs -- Juvenile literature; Tswana (African people)